Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00421-003-0832-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical demands in working life and individual physical capacity

Abstract: The purpose of this study was to investigate the prevalence of the excess of metabolic level (metabolic demands in work exceeding one-third of the individual's aerobic capacity) of working men and women today and to describe the population whose metabolic level is exceeded. A second aim was to explore how externally assessed metabolic demands match with the physical function and capacity of working men and women in jobs with the lowest and the highest demands. The aerobic power of each individual (94 men and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
(44 reference statements)
2
28
0
2
Order By: Relevance
“…An imbalance between physical work demands and cardiorespiratory fitness can be targeted either by reducing physical work demands or enhancing cardiorespiratory fitness (3,9) or the combination thereof. To our knowledge, a reduction of the relative aerobic workload by aerobic exercise has not yet been shown to be successful among blue-collar workers.…”
Section: Korshøj Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…An imbalance between physical work demands and cardiorespiratory fitness can be targeted either by reducing physical work demands or enhancing cardiorespiratory fitness (3,9) or the combination thereof. To our knowledge, a reduction of the relative aerobic workload by aerobic exercise has not yet been shown to be successful among blue-collar workers.…”
Section: Korshøj Et Almentioning
confidence: 99%
“…A high relative aerobic workload accelerates progression of arteriosclerosis (5,6), and increases the risk of myocardial infarction (7). Therefore, a balanced relationship between occupational physical activity and cardiorespiratory fitness of the worker is recommended for reducing overall risk of work-related cardiovascular overstrains (8,9). Specifically, the International Labour Organization has recommended that the average aerobic workload should not exceed 30% during an 8-hour working day (10,11).…”
mentioning
confidence: 99%
“…The women in the with group also reported more sleeping problems and had been on sick leave for musculoskeletal disorders to a higher extent than those in the without group. In addition more men in the with group than in the without group reported eczema and rated their general health status as worse, but they reported better psychological well-being (29).…”
Section: Participantsmentioning
confidence: 90%
“…The ratio between the externally assessed [interviews, [33][34][35]] physical activities of each person and his or her aerobic capacity showed that 25 (27%) of the men and 21 (22%) of the women were required to do work that exceeded their individual aerobic capacity (29).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation